Terpenóides e seu metabolismo em fungos: um estudo de Scleroderma sp. e Xylaria sp. - Gomes, Diego Zulkiewicz (Universidade Federal de São Carlos, 2011)
In the present work, the lanostane triterpenes Lanosta-8,24-diene-3β,23-diol and Lanosta-8,23-diene-3β,25-diol were isolated from the basidiomycete Scleroderma sp., an extremely rich source of triterpenes and not yet reported as having it. The molecular structures were completely determined by 1D and 2D NMR and mass spectrometry (MS) analyses with fragmentation mechanisms being also suggested. These and other substrates were considered for terpenoids metabolism study in Xylaria sp., a micro-organism known from previous projects, at the research group LaBioMMi, by living in mutuality with Sapindus saponaria, a saponins producer plant, known for its antifungal metabolites. Different substrates were considered for fungal experiments, including oleanolic acid, isolated from clove and identified by 1H NMR, stevioside, obtained from commercial source, avenacosides A and B from oats, used in its natural way (known for being rich in these glycosides) and the previously isolated lanosterols from Scleroderma sp. As in their habitat, Xylaria fungus has proved to have great glycosides affinity, promoting deglycosylations reactions or even combining them with different sugar patterns. Oleanolic acid was completely consumed by the micro-organism, while lanosterol were fully incorporated into the fungus mycelium. Using high-resolution LC/MS analysis with Q-TOF hybrid analyzer, the metabolites were accurately identified so as some biotransformation products.
Terpenoids and its metabolism in fungi: a study of Scleroderma sp. and Xylaria sp.
Keywords: Química orgânica; Biotransformação; Terpenóides; Microorganismos endofíticos; Espectrometria de massas; Produtos naturais; CIENCIAS EXATAS E DA TERRA::QUIMICA